Ultrasonography for diagnosing medial sided ankle instability in supination external rotation ankle fracture - Jirawat Saengsin; Pongpanot Sornsakrin; Pichitchai Atthakomol; Go Sato; Bart Lubberts; Gregory Waryasz; Christopher W. DiGiovanni; Daniel Guss (Journal of Orthopaedic Surgery and Research)
Abstract Background Destabilizing injuries to the deltoid ligament have relied on radiographic stress examination for diagnosis, with a focus on medial clear space widening. Increasingly, Portable ultrasound has also been used in the clinical setting, allowing dynamic and non-invasive evaluation at the point of care. The aim of this study was to determine whether portable ultrasound can detect medial sided instability associated with supination-external rotation type ankle injuries during the gravity stress, weightbearing, and external rotation stress. Methods Ten fresh-frozen cadaveric ankles were used in this study. Assessment of medial clear space distances with portable ultrasound was first performed with all structures intact, and later with sequential transection of the anterior inferior tibiofibular ligament (Stage I), Weber B fibular fracture (Stage II), posterior inferior tibiofibular ligament (Stage III), superficial deltoid ligament (Stage IVa), and the deep deltoid ligament (Stage IVb). In all scenarios, four loading conditions were considered; (1) a gravity stress test with the ankle positioned in a neutral position; (2) a gravity stress test with the ankle positioned in a plantarflexed position; (3) an external rotation stress test; and (4) simulated weightbearing condition. Results Among all four loading conditions, all medial clear space values increased as the supination-external rotation ankle injury stage progressed (Spearman’s rank correlation ranged from 0.43 to 0.90, P <.001). The medial clear space values measured with the portable ultrasound during; (1) gravity stress test in neutral ankle position, (2) gravity stress test in plantarflexed ankle position, (3) weightbearing, and (4) external rotation stress test were significantly increased between intact stage vs. stage IVb (P =.036), as well as between stage III vs. IVb (P ranged from 0.015 to 0.047). Conclusions Portable ultrasonography is a feasible tool for diagnosing medial ankle instability in supination-external rotation ankle injury. The medial clear space measurements assessed with portable ultrasound during the gravity stress test, weightbearing, and the external rotation stress test well correlated with the supination-external rotation ankle injury staging. Besides, the portable ultrasound method can differentiate the supination-external rotation ankle injury stage IVb from the intact stage, as well as differentiating the supination-external rotation ankle fracture without deltoid ligament injury (III) from the supination-external rotation stage with complete deltoid ligament injury (IVb).